Anatomy and Histology of the Sacroiliac Joints - Egund, Niels; Jurik, Anne Grethe (Seminars in Musculoskeletal Radiology, 2014)
The anatomy of joints provides an important basis for understanding the nature and imaging of pathologic lesions and their imaging appearance. This applies especially to the sacroiliac (SI) joints, which play a major role in the diagnosis of spondyloarthritis. They are composed of two different joint portions, a cartilage-covered portion ventrally and a ligamentous portion dorsally, and thus rather complex anatomically. Knowledge of anatomy and the corresponding normal imaging findings are important in the imaging diagnosis of sacroiliitis, especially by MR imaging. A certain distinction between the two joint portions by MR imaging is only obtainable by axial slice orientation. Together with a perpendicular coronal slice orientation, it provides adequate anatomical information and thereby a possibility for detecting the anatomical site of disease-specific characteristics and normal variants simulating disease. This overview describes current knowledge about the normal macroscopic and microscopic anatomy of the SI joints.
Keywords: sacroiliac joint; normal anatomy; histology; MR imaging